Solution of the energy equation of a two-phase medium taking into account heat transfer between phases - Komolova G.Sh; Djalilova T And.M.I. docent (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
In this paper, we consider the problem of supersonic flow around a gas with solid particles. When studying the flow of gas with particles in the snot, a near-wall region of the light phase was found. In a specific example, numerical calculations are made and, on the basis of the results obtained, the shape of the surface of a curvilinear angle, the distribution of pressure and temperature of the flow along the surface at various values of the diameter and concentration of particles are constructed.